Design and Synthesis of Two Indol-Steroid Derivatives - Figueroa-Valverde, L.; Díaz-Cedillo, F.; García-Cervera, E.; Pool Gómez, E.; Rosas-Nexticapa, M.; López-Ramos, M. (Asian Journal of Chemistry, 2014)
In this study two new indol-steroid derivatives were synthesized. The first stage involves the synthesis of 17-(2-amino-thiazol-5-yl)-10,13-dimethyl-1,2-6,7,8,9,10,11,12,13,14,15,16,17-tetradecahydro-cyclopenta[a]phenanthren-3-one (3) by the reaction of progesterone with thiourea using I2 as catalyst. The second stage was achieved by reaction of a brucine derivative with the compound 3 to form the compound N-(2,3-dimethoxystrychnidin-10-ylenamino)-N'-[10,13-dimethyl-17(2-amino-thiazol-5-yl)-1,2,6,7,8,9,10,11,12,13,14,15,16,17-tetradecahydro-cyclopenta-[a]phenanthren-3-ylidene]-ethane-1,2-diamine using boric acid as catalyst. The third stage was achieved by reaction of compound 3 with brucine to form 10,13-dimethyl-17-[2-(2,3- dimethoxy-strychnidin-10-ylideneamino)-thiazol-5-yl]-1,2,6,7,8,9,10,11,12,13,14,15,16,17-tetradecahydro-cyclopenta[a]phenanthren-3-onausing boric acid as catalyst. The structure of compounds obtained was confirmed by spectrometry data.